Transcriptome analysis revealed the expression levels of genes related to abscisic acid and auxin biosynthesis in grapevine (Vitis vinifera L.) under root restriction - Wang, Lei; Li, Hui; Li, Jiajia; Li, Guanhan; Zahid, Muhammad Salman; Li, Dongmei; Ma, Chao; Xu, Wenping; Song, Shiren; Li, Xiangyi; Wang, Shiping (Frontiers in Plant Science, 2022)
The root system is essential for the stable growth of plants. Roots help anchor plants in the soil and play a crucial role in water uptake, mineral nutrient absorption and endogenous phytohormone formation. Root-restriction (RR) cultivation, a powerful technique, confines plant roots to a specific soil space. In the present study, roots of one-year-old “Muscat Hamburg” grapevine under RR and control (nR) treatments harvested at 70 and 125 days after planting were used for transcriptome sequencing, and in total, 2031 (nR7 vs. nR12), 1445 (RR7 vs. RR12), 1532 (nR7 vs. RR7), and 2799 (nR12 vs. RR12) differentially expressed genes (DEGs) were identified. Gene Ontology (GO) enrichment analysis demonstrated that there were several genes involved in the response to different phytohormones, including abscisic acid (ABA), auxin (IAA), ethylene (ETH), gibberellins (GAs), and cytokinins (CTKs). Among them, multiple genes, such as PIN2 and ERF113, are involved in regulating vital plant movements by various phytohormone pathways. Moreover, following RR cultivation, DEGs were enriched in the biological processes of plant-type secondary cell wall biosynthesis, the defense response, programmed cell death involved in cell development, and the oxalate metabolic process. Furthermore, through a combined analysis of the transcriptome and previously published microRNA (miRNA) sequencing results, we found that multiple differentially expressed miRNAs (DEMs) and DEG combinations in different comparison groups exhibited opposite trends, indicating that the expression levels of miRNAs and their target genes were negatively correlated. Furthermore, RR treatment indeed significantly increased the ABA content at 125 days after planting and significantly decreased the IAA content at 70 days after planting. Under RR cultivation, most ABA biosynthesis-related genes were upregulated, while most IAA biosynthesis-related genes were downregulated. These findings lay a solid foundation for further establishing the network through which miRNAs regulate grapevine root development through target genes and for further exploring the molecular mechanism through which endogenous ABA and IAA regulate root architecture development in grapevine.